L2 Figurative Language Teaching Theory and Practice. - Galantomos, Ioannis (Cambridge Scholars Publisher, 2021)
During L2 vocabulary instruction, figurative language frustrates even highly proficient users who find it difficult to cope with non-literal expressions, such as metaphors, metonymies, and idioms. Given that figurative language is closely associated with enhanced L2 communicative competence, this volume brings together theory and teaching applications, shedding light on the comprehension and production of figurative language in a foreign language context.